Relationship between white matter integrity and serum inflammatory cytokine levels in drug-naive patients with major depressive disorder: diffusion tensor imaging study using tract-based spatial statistics - Sugimoto, Koichiro; Kakeda, Shingo; Watanabe, Keita; Katsuki, Asuka; Ueda, Issei; Igata, Natsuki; Igata, Ryohei; Abe, Osamu; Yoshimura, Reiji; Korogi, Yukunori (Translational psychiatry, 2018)
Recently, accumulated evidence has indicated a role of inflammation in the pathogenesis of major depressive disorder (MDD). Therefore, we evaluated the relationship between white matter integrity and serum cytokine levels during the first depressive episode in drug-naive MDD patients, using a tract-based spatial statistics (TBSS) method. A total of 35 drug-naive MDD patients with a first depressive episode and 35 healthy subjects (HS) underwent diffusion tensor imaging, and an analysis was conducted using TBSS. We measured serum cytokine levels (interleukin [IL]-1β, IL-6, interferon-γ, and tumor necrosis factor-α). Fractional anisotropy (FA) values of the bilateral inferior fronto-occipital fasciculus (IFOF) and genu of the corpus callosum in MDD patients were decreased significantly to the HS ( p